The school goes to the Geological Museum: Expanding and resignifying the forms of relationship with memory today (Cadernos de Sociomuseologia, 2024)
ABSTRACT:This article is about an educational activity carried out at the Lisbon Geological Museum with a group of 4th grade students. The aim of this activity is to question museums as spaces frozen in time, in order to occupy them as experiential spaces that provide opportunities for dialog between different worldviews. In this way, the museum's social commitment is strengthened with regard to current issues and problems in society and the social participation of communities in a critical and reflective way. In this case, we highlight the interaction between the museum and the school as an important inter-institutional partnership in extending education to the community and society. We begin by explaining the theoretical references that frame this proposed activity, both with regard to the field of Museology, namely from the perspective of Sociomuseology, and with regard to schools and education. Afterwards, we describe the educational action carried out, based on the presentation and journey of the Wapichana indigenous artist Gustavo Caboco, who takes us back to the worldview of his people in their relationship with memory, in order to value cultural diversity. We conclude with some final thoughts on the activity and the way the children adhered to the proposals made.Keys-word: Museum, School, Educational-Cultural Action, Memory